2003
DOI: 10.1016/s1535-6108(03)00020-5
|View full text |Cite
|
Sign up to set email alerts
|

BCR/ABL activates mdm2 mRNA translation via the La antigen

Abstract: In a BCR/ABL-expressing myeloid precursor cell line, p53 levels were markedly downmodulated. Expression of MDM2, the negative regulator of p53, was upregulated in a tyrosine kinase-dependent manner in growth factor-independent BCR/ABL-expressing cells, and in accelerated phase and blast crisis CML samples. Increased MDM2 expression was associated with enhanced mdm2 mRNA translation, which required the interaction of the La antigen with mdm2 5' UTR. Expression of MDM2 correlated with that of La and was suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
248
5
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(264 citation statements)
references
References 62 publications
8
248
5
3
Order By: Relevance
“…For example, the BCR/ABL oncoproteins activate MDM2 mRNA translation via the RNA binding protein La resulting in the downmodulation of p53. 8 Thus, cells are hardwired to respond to environmental stimuli by inducing the synthesis of protein translational machinery to coordinate cell growth (increase in cell size) with proliferation (increase in cell number). Uncoupling protein synthesis from cell growth and proliferation can result in tumorigenesis.…”
Section: Control Of Ribosome Biogenesismentioning
confidence: 99%
“…For example, the BCR/ABL oncoproteins activate MDM2 mRNA translation via the RNA binding protein La resulting in the downmodulation of p53. 8 Thus, cells are hardwired to respond to environmental stimuli by inducing the synthesis of protein translational machinery to coordinate cell growth (increase in cell size) with proliferation (increase in cell number). Uncoupling protein synthesis from cell growth and proliferation can result in tumorigenesis.…”
Section: Control Of Ribosome Biogenesismentioning
confidence: 99%
“…72 Accordingly, Northern blot hybridization of polysome-and monosomeassociated RNA separated by linear sucrose gradient centrifugation revealed that mdm2 mRNA was predominantly in the polysome-associated fractions of BCR/ABL-expressing cells, whereas it was clearly shifted toward the monosome fractions after STI571 treatment. 72 Further analysis revealed that increased mdm2 mRNA translation in BCR/ABL cells was dependent on the integrity of a 27-base nucleotide sequence of mdm2 mRNA (located between the second uORF and 36 nucleotide upstream of the main AUG) which specifically interacts with the La antigen. 72 …”
Section: Effect Of Imatinib Mesylate On Mrna Translationmentioning
confidence: 96%
“…For example, c/ebpb and p53 mRNAs, which reportedly undergo translational regulation [78][79][80][81][82] and are downregulated in BCR/ABL-transformed cells, 72,83 were less abundant (by oligonucleotidearray hybridization) in the polysome-associated mRNA fractions of untreated BCR/ABL-expressing cells, in which mdm2 mRNA levels were, instead, markedly increased. 72 Accordingly, Northern blot hybridization of polysome-and monosomeassociated RNA separated by linear sucrose gradient centrifugation revealed that mdm2 mRNA was predominantly in the polysome-associated fractions of BCR/ABL-expressing cells, whereas it was clearly shifted toward the monosome fractions after STI571 treatment. 72 Further analysis revealed that increased mdm2 mRNA translation in BCR/ABL cells was dependent on the integrity of a 27-base nucleotide sequence of mdm2 mRNA (located between the second uORF and 36 nucleotide upstream of the main AUG) which specifically interacts with the La antigen.…”
Section: Effect Of Imatinib Mesylate On Mrna Translationmentioning
confidence: 99%
See 2 more Smart Citations